Türklerin mimari mirası (İstanbul)
11 cilt (1. c. 517 sayfa ; 2. c. 507 sayfa ; 3. c. 560 sayfa ; 4. c. 446 sayfa ; 5. c. 512 sayfa ; 6. c. 528 sayfa ; 7. c. 488 sayfa ; 8. c. 512 sayfa ; 9. c. 503 sayfa ; 10. c. 519 sayfa ; 11. c. 530 sayfa)